Product relatedness role on driving industrial policy success - Cardoso, Samuel Marcelino Belchior (2018)
This thesis aims to study how product relatedness to the current pattern of specialization influences the success of industrial policies in underdeveloped sectors. Drawing from Hausmann and Klinger (2006), this work extends the existing literature on the importance of proximity spillovers to explain economic development by focusing on underdeveloped sectors. We find that investment's success in an underdeveloped sector is more likely if it is highly related to the current pattern of specialization. However, heterogeneity amongst sectors is remarkable. Moreover, industrial policy cases are sometimes successful despite the bad odds provided by this criterion, suggesting further factors should be considered.